Cardiac and hemodynamic consequences during capnoperitoneum and steep Trendelenburg positioning: lessons learned from robot-assisted laparoscopic prostatectomy - Rosendal, Christian; Markin, Sergei; Hien, Maximilian; Motsch, Johann; Roggenbach, Jens (Journal of clinical anesthesia, 2014)
Study Objective - To determine and interpret the changes in preload, afterload, and cardiac function in the different phases of robot-assisted laparoscopic prostatectomy. - Design - Prospective, observational monocenter study. - Setting - Operating room at a university hospital. - Patients - 31 consecutive, ASA physical status 1, 2, and 3 patients. - Interventions - Observations were made at 5 distinct time points: baseline after induction of anesthesia, after initiation of capnoperitoneum, immediately after a 45° head-down tilt, 15 minutes after the 45° head-down tilt was established, after the release of the capnoperitoneum, and 5 minutes after the patient was returned to a horizontal position (end). - Measurements - Transpulmonary thermodilution and pulse contour analysis were used to record hemodynamic changes in preload, afterload, and cardiac function. - Main Results - While central venous pressure increased threefold from baseline, none of the other preload parameters showed excessive fluid overload or demand. There was no significant change in cardiac contractility over time. Afterload increased significantly during the capnoperitoneum and significantly decreased compared with baseline after the release of abdominal pressure at the end of the procedure. Heart rate and cardiac index increased significantly during robot-assisted laparoscopic prostatectomy. - Conclusions - Selective arterial vasodilation at the time of capnoperitoneum may normalize afterload and myocardial oxygen demand.